(3GdeSJUaj ef Sff GdeUWais - (3CHh YHO Gddg eMeO Hf SYjO Hf eYf GdbQjWj,J (B576 (3g` s ((3CMeO Hf Ydi Hf CMeO Hf SdjeGf Hf eMeO GdLMjai GdYjSi s)
(3ChdgG (B:s
(3Cf GdMeO ddg , fSJYjfg hfSJZaQg, hfYhPP HGddg ef TQhQ CfaSfG ef jgOi Gddg agh GdegJOi s
(3BNQgG (B:s
(3abGd QShd Gddg (B( (3U(B) (3CSLY cSLY GdEYQGH , hLYd Ydjge GdOjI Je GdLRA GdChd HMeO Gddg hefg s
(3HChdgG bQGAI SfI (B960(3g` hGdfSNI ebGHdIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdMOjK h GdeUWdMs